Democracy between consolidation and crisis : parties, groups, and citizens in Southern Europe / Leonardo Morlino. - Morlino, Leonardo, 1947- (Oxford studies in democratization., 1998)
The second half of the 20th century has witnessed several waves of democratization throughout the world. Based on a systematic analysis of four Southern European countries, this text identifies several key aspects of democratic consolidation.